2019
DOI: 10.1088/1361-6668/ab0799
|View full text |Cite
|
Sign up to set email alerts
|

A high speed and high efficiency superconducting photon number resolving detector

Abstract: A series superconducting nanowire single-photon detector is a high performance nanowire array detector that has the potential to reach a high system detection efficiency (SQE), a high counting rate (CR) and photon number resolving functionality. Interconnected with a simplified readout, it shows promise for large scale expansion and has good prospects for future applications in single-photon imaging, quantum optics, quantum computing and deep-space communication. In this paper, we demonstrate a high SQE and CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Recently, we fabricated a large area (∼20 × 20 μm 2 ) SND with a total kinetic inductance of 1.25 μH, which had a pulse recovery time of ∼50 ns, but the PNR detector demonstrated a potential of high counting rate [14]. In this work, we found that the increase of counting rates was attributed to the series array architecture and the weak dependence of detection efficiency on bias current.…”
Section: Introductionmentioning
confidence: 87%
“…Recently, we fabricated a large area (∼20 × 20 μm 2 ) SND with a total kinetic inductance of 1.25 μH, which had a pulse recovery time of ∼50 ns, but the PNR detector demonstrated a potential of high counting rate [14]. In this work, we found that the increase of counting rates was attributed to the series array architecture and the weak dependence of detection efficiency on bias current.…”
Section: Introductionmentioning
confidence: 87%
“…Although SNSPDs were initially incapable of distinguishing between single and multi-photon events much progress has been made in recent years. Various schemes exist including exploiting the rise time variation between different n-photon events [49] or connecting multiple nanowires in series [50,51].…”
Section: Photon Number Resolutionmentioning
confidence: 99%
“…Although recent work has shown that some photon number resolution can be recovered directly from the output of the detector by modifying the bias circuitry [7][8][9][10], in standard operation, however, these detectors do not resolve the number of photons incident. To overcome this, SNSPDs can be multiplexed in arrays, either spatial [11][12][13][14][15][16][17][18][19][20][21][22][23][24] or temporal [25][26][27], such that the number of pixels in the array that fire gives some information about the number of photons that were incident.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their low noise, high timing resolution and excellent efficiency across a broad wavelength range, superconducting nanowire single photon detectors (SNSPDs) have become increasingly prevalent in low-photon-flux optical sensing [1][2][3][4][5]. Advances in fabrication yield and read-out techniques [6][7][8][9][10][11][12] have enabled arrays of such detectors to be developed [13][14][15][16][17][18][19][20][21][22][23][24], which have lead to applications in imaging [20,25,26] and deep space communication [27]. Such devices are also ideal for multiplexed photon counting in quantum optics experiments.…”
Section: Introductionmentioning
confidence: 99%